2016
DOI: 10.1002/anie.201511521
|View full text |Cite|
|
Sign up to set email alerts
|

Substrate‐Controlled Product Divergence: Conversion of CO2 into Heterocyclic Products

Abstract: Substituted epoxy alcohols and amines allow substrate-controlled conversion of CO2 into a wide range of heterocyclic structures through different mechanistic manifolds. This new approach results in an unusual scope of CO2-derived products by initial activation of CO2 through either the amine or alcohol unit, thus providing nucleophiles for intramolecular epoxy ring opening under mild reaction conditions. Control experiments support the crucial role of the amine/alcohol fragment in this process with the nucleop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 59 publications
4
86
1
Order By: Relevance
“…[13] To our delight, the high yield obtained of 3 a (92 % yield) was the general trend observed for several anilines with either electron-donating (Me, tBu, OMe) or -withdrawing (Cl) substituents (3 b-j, 72-92 %), with the notable exception of NO 2 that diminished enough the nucleophilicity to prevent any conversion (3 d). Notably, we also found that the reaction tolerates rather well the presence of a coordinating heteroatom (3 w, 64 %), or severe steric hindrance near the reaction site (3 x, 75 %).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…[13] To our delight, the high yield obtained of 3 a (92 % yield) was the general trend observed for several anilines with either electron-donating (Me, tBu, OMe) or -withdrawing (Cl) substituents (3 b-j, 72-92 %), with the notable exception of NO 2 that diminished enough the nucleophilicity to prevent any conversion (3 d). Notably, we also found that the reaction tolerates rather well the presence of a coordinating heteroatom (3 w, 64 %), or severe steric hindrance near the reaction site (3 x, 75 %).…”
supporting
confidence: 60%
“…[12] Alternatively, two reports this year have disclosed the construction of NAOs by fixating simultaneously CO 2 into anilines and epoxides. [13] A contribution by Kleij and co-workers describes the partnership of a Al-based Lewis acid with a source of bromide to effectively catalyze the conversion of epoxy amines into NAOs at room temperature, yet using 10 bar of CO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al 97 reported CuI-catalyzed cyclization of primary amine carbamate salts with aldehydes and aromatic terminal alkynes. In 2015, Kleij and coworkers 98 reported the synthesis of racemic oxazolidinones from epoxy amines (Scheme 21A). A mechanistic investigation with an enantiopure epoxy alcohol showed chirality inversion at the β-carbon, implying that the reaction likely proceeds through an intramolecular attack at the β-carbon.…”
Section: Scheme 19mentioning
confidence: 99%
“…The reactionp roceeded with high activity (initial turnover frequency of 1680 h À1 for EtOH) and selectivity( > 95 %) toward the formation of twelve monoalkyl glyceryl ethers (MAGEs) in ar egioselective fashion (84-96 %y ield of the non-symmetric regioisomer). [12][13][14] We have recentlys hown that GLYc an be conveniently obtained as a value-added product from biobasedepichlorohydrin (ECH) productionp lants (EPICEROL process, Solvay), [15] thereby enhancing the environmental sustainability of the entireE CH chain as well as interest towards GLYc onversiont ov aluable chemicals such as polymers, [16] drugs, [17] diols, [18][19][20] solketal, [21,22] and organic carbonates. [1][2][3][4][5][6][7] In particular, since the discoveryo fm anyu seful synthetic strategies that have given access to aw ide variety of chiral epoxides, this reaction has becomeani mportant entry in the toolbox of organic synthesis for obtaining enantiopure molecules.…”
mentioning
confidence: 99%